Pedagogical Strategies for Writing Development Among Elementary School Students - Castro Zapata, Edgar Ivan (Íkala, Revista de Lenguaje y Cultura, 2022)
In the early stage of students’ instruction, difficulties arise during the development of skills required for academic, intellectual and emotional performance. These are related particulary to the acquisition of writing. This study, with a mixed approach, exploratory sequential design, derivative modality and descriptive scope, identified the problems evidenced by second grade students of a public educational institution in Colombia, in their process of acquiring writing, and their relationship with the pedagogical strategies used by teachers. The research started with a qualitative analysis of observed and studied variables, and then gave way to a quantitative study. The results indicate that there is a need to promote motor development, so that problems, which have generated difficulty in writing, such as strong strokes, weak strokes, inconsistent spellings and absence of graphs in words. In addition, they show that the pedagogical strategies used by the teachers achieved significant advances such as a small amount of omission, inversion and distortion of spellings in the students’ writings.